Excellent real‐world outcomes of adults with Burkitt lymphoma treated with CODOX‐M/IVAC plus or minus rituximab. (9th May 2018) - Zhu, Katie Y.; Song, Kevin W.; Connors, Joseph M.; Leitch, Heather; Barnett, Michael J.; Ramadan, Khaled; Slack, Graham W.; Abou Mourad, Yasser; Forrest, Donna L.; Hogge, Donna E.; Nantel, Stephen H.; Narayanan, Sujaatha; et al.
Summary: Treatment of Burkitt lymphoma (BL) with intensive, multi‐agent chemotherapy with aggressive central nervous system (CNS) prophylaxis results in high cure rates, although no regimen is standard of care. We examined population‐based survival outcomes of adults with BL treated with a modified combination of cyclophosphamide, vincristine, doxorubicin, prednisone and systemic high‐dose methotrexate (MTX) (CODOX‐M) with IVAC (ifosfamide, mesna, etoposide, cytarabine and intrathecal MTX) (CODOX‐M/IVAC) ± rituximab over a 15‐year period in British Columbia. For the 81 patients identified (including 8 with CNS involvement and 18 with human immunodeficiency virus‐associated BL), 5‐year progression‐free survival (PFS) and overall survival (OS) were 75% [95% confidence interval (CI): 63–83%] and 77% (95% CI: 66–85%), respectively, with no treatment‐related deaths. Those who completed the regimen per protocol ( n  = 38) had significantly improved 5‐year PFS 86% ( P  = 0·04) and OS 92% ( P  = 0·008), as did those under 60 years with 5‐year PFS 82% ( P  = 0·005) and OS 86% ( P  = 0·002), which remained significant in multivariate analysis [PFS: hazard ratio (HR) 3·36, P  = 0·018; OS HR 4·03, P  = 0·012]. Incorporation of high‐dose systemic methotrexate also significantly affected multivariate survival outcomes (OS HR 0·28, P  = 0·025). Stem cell transplant in first remission had no effect on OS or PFS. This large, real‐world analysis of BL patients treated with CODOX‐M/IVAC ± rituximab demonstrates excellent survival outcomes comparable to clinical trials. These results help to serve as a benchmark when comparing curative therapies for BL patients as novel regimens are incorporated into clinical practice.